Portofolio Reksadana Optimal Saham Bluechip pada Kondisi Pasar Saham Bearish dan Bullish - Mohammad Yahya Arief (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2019)
In bullish and bearish markets, investors should seek the optimization of investments in the mutual funds. This research attempted to elaborate on how to divide funds that are less productive for the investors in accordance with the slogan, “don’t pull all of your eggs in one basket”; so that the objective of the return portfolio obtained becomes maximum, and the risk of the return becomes minimum all at once. By the operational and technical study, the data were analyzed by the goal programming model formulation and the simulation of the priorities. The results of the goal programming optimization analysis showed that in bearish market, the investors are risk averse who keep retaining the funds in the form of cash, at least 20% of cash to maintain the liquidity. As in the bearish market, it is not easy to trade the owned stocks although it is categorized as bluechip stocks. The risk averse investors will also invest the funds at the minimum rate (IDR 20,000,000) on the stock with the lowest return risk, i.e. TLKM stocks. For the risk-seeking investors, they will also optimize the investment of the stocks portfolio with a similar pattern; nonetheless, it is significantly different from the investment into BUMI stocks. The risk-seeking investors invest the funds with the largest proportion of BUMI stocks, while the risk averse investors invest in the smallest proportion. In contrast, in the bullish market, both risk averse and risk seeking investors leave no part of the funds in cash. Both types of investors precisely maximize the investment proportion in BUMI stocks.Keywords: bluechip stocks, bullish markets, bearish market, the goal programmingAbstrak: Pada pasar bullish dan bearish, investor harus mengupayakan optimasi investasinya dalam reksadana. Penelitian ini mencoba menjelaskan bagaimana membagi dana yang kurang produktif bagi investor, sesuai dengan slogan don’t pull all of your eggs in one basket; agar tujuan perolehan return portofolio menjadi maksimum dan sekaligus resiko return-nya menjadi minimum. Dengan kajian teknis operasional data dianalisis dengan formulasi model goal programming dan simulasi prioritas kepentingan. Hasil penelitian analisis optimasi goal programming menunjukkan bahwa pada saat pasar bearish, investor risk averter, selayaknya tetap menyisakan dananya dalam bentuk uang kas minimal 20% untuk menjaga likuiditas, karena pada pasar bearish tidak mudah memperjual-belikan saham yang dimiliki, walaupun saham itu terkatagori bluechip. Investor risk averter ini juga akan menginvestasikan dananya pada tingkat minimal (Rp20 juta) pada saham dengan resiko return terendah, yaitu saham TLKM. Untuk investor risk seeker, juga akan mengoptimalkan investasi portofolio saham dengan pola yang mirip. Namun, berbeda signifikan dalam investasi ke saham BUMI. Investor risk seeker menginvestasikan dana dengan proporsi terbesar pada saham BUMI. Sementara itu, investor risk averter dalam proporsi terkecil. Sebaliknya, pada pasar bullish baik investor risk averter maupun risk seeker tidak menyisakan sebagian dananya dalam bentuk kas. Kedua jenis investor tersebut justru memaksimumkan proporsi investasinya pada saham BUMI.Kata kunci: saham bluechip, pasar bullish, pasar bearish, goal programming